Military Neurosurgery Socioeconomic Data: Benefits, Challenges, and Opportunities. Issue 5 (15th November 2017) - Menger, Richard; Robbins, J Will; Bell, Randy
Abstract: Military conflict and neurosurgery date back to antiquity. Neurosurgery's development is intimately linked with Harvey Cushing's military experience. Previous papers highlighted unique opportunities and socioeconomic challenges facing military neurosurgeons. Here, we provide objective data from military neurosurgeons surrounding these issues. Internet survey responses were solicited from current, separated, and retired military neurosurgeons regarding workforce issues and their perception of military neurosurgery. A total of 80.9% (98/121) of respondents enjoyed their military experience, 63.6% (77/121) were very pleased with their service; 97.4% (114/117) enjoyed treating military patients, and 78.2% (93/119) would recommend military service. Positives included feelings of patriotism (87.4%), development of camaraderie (71.4%), and deployment experience (93.8%). However, 76.5% of respondents noted concerns regarding military and civilian pay disparity. 37.5% were overwhelmed with administrative responsibilities, and over 50% desired higher case volume. Multivariate analysis showed those who failed to develop a sense of camaraderie were more likely to be dissatisfied ( P = .02). Those still currently serving trended towards dissatisfaction ( P = .08), and current military neurosurgeons were only 0.29 times as likely to recommend military service to another neurosurgeon as compared to those who were retired or separated ( P < .024). Service as a military neurosurgeon is an overwhelmingly positive experience but opportunities exist for mechanisms to increase operative case load, reduce administrative responsibilities, and reduce military–civilian income disparity. Addressing these issues is important as current military neurosurgeons were more likely to be dissatisfied with their military experience and less likely to recommend military service to another neurosurgeon.